COMPRESSIVE STRENGTH OF Ca(OH)2 COMBINED WITH MUSA ACUMINATA AS A PULP CAPPING MATERIAL - Agung Satria Wardhana; Andres Migael Hidalgo; Dewi Puspitasari; Isyana Erlita; Alexander Sitepu (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: The weakness of Ca(OH)2 is its low compressive strength and mechanical properties which can affect the stability of the material to the liquid in the tooth root canal so that it can dissolve the root canal medicament material. Due to the various weaknesses of Ca(OH)2, the researchers are interested in combining Ca(OH)2 with natural ingredients extracted from Musa acuminata (Mauli Banana) stem. Musa acuminata stem extract  (MaSE) contains bioactive compounds such as tannins, saponins, alkaloids, flavonoids and lycopene which have antioxidant, anti-inflammatory, antibacterial and anti-viral properties. One of the requirements for pulp capping material is to have sufficient compressive strength, therefore, it is necessary to conduct research to test the value of the compressive strength of the combination of Ca(OH)2 with Musa acuminata stem extract. Purpose: To analyze the compressive strength of the pulp capping material from the combination of calcium hydroxide and Musa acuminata stem extract, with a ratio of 1:1; 1:1.5 ; and 1.5:1. Method: This research is a pure experimental study with a posttest-only design with a control group design, consisting of 4 treatment groups, including: group 1 the combination of Ca(OH)2 with Musa acuminata stem extract at 1:1, group 2 1:1.5, group 3 1.5:1, and group 4 as a positive control. Results: One Way Anova test (p<0.05) which means there is a significant difference. Data analysis was continued with the LSD Post Hoc test (p<0.05) which showed that there were significant differences between groups, between each treatment group. Conclusion: The combination of Ca(OH)2 with 50% MaSE and PG ratio of 1.5 : 1 : 0.375, has the highest compressive strength (1.40 MPa), so it can be concluded that the more Musa acuminata stem extract in the combination, the lower the compressive strength. Keywords : Calcium hydroxide, Compressive strength, Musa acuminata stem extract